Tau Knockout and α-Synuclein A53T Synergy Modulated Parvalbumin-Positive Neurons Degeneration Staging in Substantia Nigra Pars Reticulata of Parkinson’s Disease-Liked Model - Zheng, Meige; Liu, Yanchang; Xiao, Zhaoming; Jiao, Luyan; Lin, Xian (Frontiers in Aging Neuroscience, 2022)
The loss of parvalbumin-positive (PV+) neurons in the substantia nigra pars reticulata (SNR) was observed in patients with end-stage Parkinson’s disease (PD) and our previously constructed old-aged Pitx3-A53Tα-Syn × Tau–/– triple transgenic mice model of PD. The aim of this study was to examine the progress of PV+ neurons loss. We demonstrated that, as compared with non-transgenic (nTg) mice, the accumulation of α-synuclein in the SNR of aged Pitx3-A53Tα-Syn × Tau–/– mice was increased obviously, which was accompanied by the considerable degeneration of PV+ neurons and the massive generation of apoptotic NeuN+TUNEL+ co-staining neurons. Interestingly, PV was not costained with TUNEL, a marker of apoptosis. PV+ neurons in the SNR may undergo a transitional stage from decreased expression of PV to increased expression of NeuN and then to TUNEL expression. In addition, the degeneration of PV+ neurons and the expression of NeuN were rarely observed in the SNR of nTg and the other triple transgenic mice. Hence, we propose that Tau knockout and α-syn A53T synergy modulate PV+ neurons degeneration staging in the SNR of aged PD-liked mice model, and NeuN may be suited for an indicator that suggests degeneration of SNR PV+ neurons. However, the molecular mechanism needs to be further investigated.